PREVALENSI NYERI PUNGGUNG BAWAH SEDERHANA DAN FAKTOR YANG BERPENGARUH PADA PEKERJA ANGKAT ANGKUT MANUAL - Shierly Halim* (NEURONA, 2010)
INTRODUCTION AROUND 50 LABOURS HAVE SIMPLE LOW BACK PAIN PER YEAR THE AWKWARD POSITION DURING LIFTING WITH OVER LIMIT HAS BEEN SUGGESTED BY NATIONAL INSTITUTE FOR OCCUPATIONAL SAFETY AND HEALTH NIOSH COULD BE A POTENTIAL RISK OF BACK INJURY THIS STUDY AIMS TO IDENTIFY PREVALENCE OF SIMPLE LOW BACK PAIN LBP AND AFFECTED FACTORS OF MANUAL HANDLING LABOURS